Gladstone's Religion - Ramm, Agatha (The historical journal, 1985)
There were many passing phases in the eighty-eight years of Gladstone's life. ‘What did last, all through his life, was his overwhelming interest in religion and his incessant preoccupation with religious doctrine.’ ‘It is commonly supposed that there are things in life without religious significance, but this is not so. There is no human activity without its religious motives and its religious use.’ Such was the profession of the young M.P. for Newark in 1835. This article then is addressed, not to Gladstone's personal religion, which would have meant telling the story of his life, but to his attitude to religion – to his anglicanism.